An Anatomy of the Soul In English Renaissance Religious Poetry - Pope, Johnathan (My University, 2009)
This dissertation examines the centrality of the soul-body relationship to the construction of identity in English Renaissance religious poetry. The expanding field of 'body criticism' has greatly increased our understanding of the early modern body, but critics have rarely considered how Christianity influenced the ways the early moderns thought about their bodies and their embodied souls at a time when the science of anatomy flourished in Europe. Consequently, our current perception of the early modern subject is skewed. This dissertation addresses this critical gap by exploring the persistence of Christian narratives in discussions of both the body and the soul throughout the sixteenth and seventeenth centuries. The first two chapters address two interrelated question: how did early modern anatomists understand the soul, and how did early modern religious writers understand the body? This dissertation begins by examining the religious perspectives that are evident in English anatomical writing and then moves on to explore the presence of anatomical perspectives in English religious writing on the soul in order to discuss the intimate relationship between corporeality and spirituality. The final two chapters focus on the devotional poetry of An Collins and the devotional emblems of Francis Quarles in order to demonstrate the integration of a Christianized sense of corporeality into meditations on religious subjectivity. Both writers draw on the issues discussed in the first two chapters but represent corporeality differently. On the one hand, Collins transforms physical suffering into a sign of her salvation. On the other hand, Quarles expresses anxiety over the world's ability to infect the soul through the body. In both cases, the relationship between body and soul is a central concern, and their representation of that relationship is indebted to a Christianized sense of embodiment.
An Anatomy of the Soul
Keywords: soul, body, soul-body relationship, identity, religous poetry, Christianity, moderns, anatomy, An Collins, Francis Quarles, meditiations, religion